Impact of butyric acid on butanol formation by Clostridium pasteurianum. (November 2015) - Regestein, Lars; Doerr, Eric Will; Staaden, Antje; Rehmann, Lars
Highlights: Butanol yield from glycerol can be increased through butyric acid. Butyric acid conversion requires primary carbon source. Butyric acid uptake only at low pH. Online process data shows metabolic switches. Abstract: The butanol yield of the classic fermentative acetone–butanol–ethanol (ABE) process has been enhanced in the past decades through the development of better strains and advanced process design. Nevertheless, by-product formation and the incomplete conversion of intermediates still decrease the butanol yield. This study demonstrates the potential of increasing the butanol yield from glycerol though the addition of small amounts of butyric acid. The impact of butyric acid was investigated in a 7 L stirred tank reactor. The results of this study show the positive impact of butyric acid on butanol yield under pH controlled conditions and the metabolic stages were monitored via online measurement of carbon dioxide formation, pH value and redox potential. Butyric acid could significantly increase the butanol yield at low pH values if sufficient quantities of primary carbon source (glycerol) were present.